On the Reliability of Constantine Porphyrogenitus’ Account of the “Flight” of Prince Časlav from Bulgaria - Leszka, Mirosław J. (Studia Ceranea, 2017)
The present text aims to reflect on the reliability of Constantine Porphyrogenitus’ account about the departure of Časlav, a Serbian prince, from Bulgaria at the beginning of the reign of Peter I, the successor of Symeon. The passage devoted to this event is located in the De administrando imperio (32, p. 159, 161) by the learned emperor. Constantine Porphyrogenitus’ relation about the “flight” of Časlav to Serbia should be treated as manipulated and approached with considerable caution.